Sensual and sensory experiences in the Middle Ages : on pleasure, fear, desire and pain - Muntaner i Alsina, Carme; Carrillo-Rangel, David; Nieto-Isabel, Delfi I.; Castell Granados, Pau, 1984-; Castell Granados, Pau, 1984- (Cambridge Scholars Publishing, 2017)
Where was the line between pleasure and irritation in the sensory overload caused by the sounds, colours, and smells of a medieval market? How could pain and suffering be relieved by hoping for, and desiring to experience, an intimate, almost familiar, contact with Christ? This volume shows the different aspects of sensory experiences that medieval people conveyed through documents, literary accounts, and religious practices. The unifying theme here is how pleasure, pain, desire, and fear appear in different--sometimes conflicting--combinations and settings: from the private space of the monas.